Implementasi Backdoor Scanner Tool Menggunakan Metode Carving File Pada Server Codepolitan - Wijayanto, Tri; Susilo, Andi (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
Backdoor or commonly also known as the web shell is one malware (malicious code) used by hackers to attack the system that has been entered, Backdoor that has been inserted will give free access to the attacker to do things that should not be done except by web admin. Nowadays Backdoor is not just in the form of a script file, to trick Backdoor admin can also be inserted into other files like image file, lack of validation facility provided by programming language often used by hacker to upload images that have been inserted Backdoor. In this thesis will be designed tool that can recognize a Backdoor in the form of PHP source code, and in the form of image. From the results of research that has been done found that there are two types of Backdoor in the form of Source Code PHP that is in the form of content that is not encrypted and encrypted, Backdoor files are not encrypted penditeksianya using three types of selection in accordance with the three functions: manipulate the database, manipulate the directory / file, can read the identity of the running system, encrypted Backdoor file pengenkripsianya using base64, And Backdoor files in the form of detection image is done using carving method. Carving methods performed on the image file must be converted into hexadecimal form, since the results obtained from the reading of the byte file magic are not all ASCII shaped.